Comparing surgical outcomes in end-bearing amputation stumps: a prospective cohort study of different surgical techniques - Agwulonu, Ifeanyi; Idowu, Oluwaseyi; Osuala, Chinoso; Oyewunmi, Moses O.; Hakeem, Badmus (International Journal of Research in Medical Sciences, 2025)
Background: Lower limb amputation outcomes are influenced by surgical technique, which impacts stump stability, prosthetic fitting, and complication rates. This study compared postoperative outcomes of fascia-to-fascia (including fascia-to-periosteum), myodesis, and myoplasty in below-knee amputations. Methods: A five-year retrospective cohort study at two Nigerian tertiary centers included 96 adults who underwent unilateral below-knee amputation between January 2019 and December 2024. Data on patient characteristics, operative details, and outcomes were analyzed using Chi-square/Fisher’s exact tests and Kruskal-Wallis tests. Results: Mean age was 46.9±12.8 years; 69.8% were male. Fascia to fascia achieved the best prosthetic fitting (48.4%) and stump stability (49.1%), with the lowest reoperation (6.7%) and infection rates (15.2%). Myodesis had the highest reoperation and infection rates, while myoplasty had the shortest surgery time and lowest pain. fascia-to-fascia (including fascia-to-periosteum), took longest to perform (125±15 minutes) and had the highest pain scores. Conclusions: Fascia to fascia fixation appears superior for long term stump integrity and prosthetic function, which is particularly valuable in resource limited Nigerian settings. Nevertheless, its association with greater pain and longer operative time highlights the need for targeted strategies to optimise analgesia and surgical efficiency without compromising outcomes.